The Process of Establishing and Activities of the Anak Krakatau Mountain - Oktavia Ariyanti; Rio Maulana Fattah (USN Kolaka, 2020)
Anak Krakatau is one of the legendary mountains which was the result of the eruption of Mount Krakatau in 1883. The Krakatau area was divided into three regions, Krakatau Island, Sertung Island, and Mount Anak Krakatau. The activity of Mount Anak Krakatau in 1929 tended to be active, because in a year Anak Krakatau could experience eight eruptions. This can be seen in visual observations starting from 1929-2000 experiencing a fairly rapid development. At the end of 2018, Anak Krakatau erupted again, where the eruption caused a landslide to part of the mountain's side. As a result, the debris from the landslide, made the waters of the Sunda Strait unstable, thus forming a tsunami wave. Eruption did not only happened in 2018, Recently, Anak Krakatau became active again in 2020 by releasing its volcanic ash. The activity of Anak Krakatau which underlies the purpose of this study, namely knowing the formation process and activities of Mount Anak Krakatau. So that in the future further research can be carried out related to disaster mitigation efforts from the eruption of Mount Anak Krakatau in the area around the mountain. The analysis process used is a literature study using related journal articles and data on the cataclysmic events of the Anak Krakatau volcano eruption.